Delicate and diverse: A taxonomic monograph with a phylogenetic analysis of the Neotropical genus Ghilianella Spinola (Hemiptera: Reduviidae: Emesinae) - Castro-Huertas, Valentina; Forero, Dimitri; Grazia, Jocelia (Zootaxa, 2020)
The Neotropical thread-legged bug genus Ghilianella Spinola, 1850 is the most diversified within Metapterini. A taxonomic revision of Ghilianella is presented, in which seventy seven species are recognized as valid, with twenty-one described as new: Ghilianella berengeri sp. nov.; Ghilianella bifurcata sp. nov.; Ghilianella bolivari sp. nov.; Ghilianella caldensis sp. nov.; Ghilianella dilatata sp. nov.; Ghilianella embera sp. nov.; Ghilianella fernandezi sp. nov.; Ghilianella ferruginosa sp. nov.; Ghilianella gilsantanai sp. nov.; Ghilianella goliath sp. nov.; Ghilianella gracilis sp. nov.; Ghilianella huaorani sp. nov.; Ghilianella jaguar sp. nov.; Ghilianella laticauda sp. nov.; Ghilianella maricruzae sp. nov.; Ghilianella quimbaya sp. nov.; Ghilianella scimitarra sp. nov.; Ghilianella tica sp. nov.; Ghilianella urbanoi sp. nov.; Ghilianella ventrimaculata sp. nov.; and Ghilianella weirauchae sp. nov. For the first time a female specimen is described for Ghilianella atriclava Bergroth, 1911, Ghilianella colona McAtee & Malloch, 1925 and Ghilianella pachitea McAtee & Malloch, 1925. Three new synonyms are recognized: Ghilianella bulbifera Champion, 1898 (=Ghilianella pendula McAtee & Malloch, 1925 syn. nov.; Ghilianella inflata Maldonado, 1981 syn. nov.) and Ghilianella strigata McAtee & Malloch, 1925 (=Ghilianella fenestrata Maldonado, 1960 syn. nov.). Eleven species are considered nomina dubia and one species nomen nudum. A key to species and digital images of the external morphology and genitalic structures for each species are provided. Additionally, we offer the first phylogenetic hypothesis of relationships within Ghilianella, using cladistic methods. Based on the phylogenetic results we dismiss all subgenera in Ghilianella and discuss the complex evolution of the abdominal expansions.